Fronto-Parietal Contributions to Phonological Processes in Successful Artificial Grammar Learning - Goranskaya, Dariya; Kreitewolf, Jens; Mueller, Jutta L.; Friederici, Angela D.; Hartwigsen, Gesa (Frontiers in Human Neuroscience, 2016)
Sensitivity to regularities plays a crucial role in the acquisition of various linguistic features from spoken language input. Artificial grammar (AG) learning paradigms explore pattern recognition abilities in a set of structured sequences (i.e. of syllables or letters). In the present study, we investigated the functional underpinnings of learning phonological regularities in auditorily presented syllable sequences. While previous neuroimaging studies either focused on functional differences between the processing of correct vs. incorrect sequences or between different levels of sequence complexity, here the focus is on the neural foundation of the actual learning success. During functional magnetic resonance imaging (fMRI), participants were exposed to a set of syllable sequences with an underlying phonological rule system, known to ensure performance differences between participants. We expected that successful learning and rule application would require phonological segmentation and phoneme comparison. As an outcome of four alternating learning and test fMRI sessions, participants split into successful learners and non-learners. Relative to non-learners, successful learners showed increased task-related activity in a fronto-parietal network of brain areas encompassing the left lateral premotor cortex as well as bilateral superior and inferior parietal cortices during both learning and rule application. These areas were previously associated with phonological segmentation, phoneme comparison and verbal working memory. Based on these activity patterns and the phonological strategies for rule acquisition and application, we argue that successful learning and processing of complex phonological rules in our paradigm is mediated via a fronto-parietal network for phonological processes.